ANALYSIS OF ACADEMIC SUPERVISION MANAGEMENT IN IMPROVING SCHOOL QUALITY - Sumiati SUMIATI; Hery MULJONO (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2020)
This study aims to describe and analyze the effectiveness of academic supervision management in improving the quality of schools at SDIT Darul Abidin. This research uses descriptive qualitative method. The research informants were deputy principals, teachers, school committees, and supervisors of the SD Depok City Education Office. The results of the study can be concluded that the principal in his efforts to improve the quality of the school has carried out the management of academic supervision planning properly, namely: setting supervision goals as a strategic school program, forming an academic supervision team, making academic supervision instruments, schedule for academic supervision, socialization of academic supervision activities, and planning for adaptive academic supervision during the Covid-19 pandemic.The management of the implementation of academic supervision is able to encourage the habituation of quality assurance of learning services to students, namely teachers are given direction and input in making learning preparations, ensure learning is effective, creative and fun for students,direct and individual supervision techniques, and academic supervision instruments.Evaluation management and follow-up academic supervision include the following: the results of the evaluation of academic supervision are used to provide input and direction to teachers in order to help improve their competence, reporting of learning outcomes is transparent and can be accessed by students, parents of students, school leaders , supervisors of elementary school and foundation supervisors. Academic supervision management is needed because it is very important to help teachers improve their competence in ensuring the quality of learning.